2011 IEEE International Conference on Rehabilitation Robotics 2011
DOI: 10.1109/icorr.2011.5975347
|View full text |Cite
|
Sign up to set email alerts
|

Knee orthopaedic device how robotic technology can improve outcome in knee rehabilitation

Abstract: Following knee injury or surgery, knee rehabilitation therapy is an essential step to recover normal joint function for daily activities. Physical rehabilitation can take several weeks or even months until full range of motion and joint flexibility are regained. Knee rehabilitation will lead to satisfactory results only at the condition that exercises are performed regularly. An important part in knee rehabilitation is the patellar mobilization which is nowadays performed manually by the physical therapist. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Koller-Hodac et al introduced a robot-assisted knee device that can be used at home to acquire a full ROM and joint flexibility after knee surgery [1]. A narrative review by Sicuri et al suggested that it was reasonable to consider robotic rehabilitation of the shoulder for instability, stiffness, joint replacement, rotator cuff tear or other tendon ruptures [36].…”
Section: Robotic Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Koller-Hodac et al introduced a robot-assisted knee device that can be used at home to acquire a full ROM and joint flexibility after knee surgery [1]. A narrative review by Sicuri et al suggested that it was reasonable to consider robotic rehabilitation of the shoulder for instability, stiffness, joint replacement, rotator cuff tear or other tendon ruptures [36].…”
Section: Robotic Devicesmentioning
confidence: 99%
“…With an ageing population, the number of patients affected by orthopaedic conditions that either require rehabilitation alone or surgical intervention and subsequent rehabilitation are on the rise [1,2]. As the demand for rehabilitation increases, advanced rehabilitation technology has also developed, but its role and efficacy are not always appreciated by surgeons or therapists.…”
Section: Introductionmentioning
confidence: 99%
“…The University of Applied Sciences Rapperswil, Switzerland [1], proposes an automatic device that performs therapy exercises and record of progress. Others works propose alternatives to mimic the physiotherapist intervention as the "Knee rehabilitation using an intelligent robotic system" [2] that propose a rule based intelligent control and Therapeutic Exercise Machine (TEM) [3], which memorizes movements, guided by the therapist, and reproduces them afterwards.…”
Section: Introductionmentioning
confidence: 99%
“…3 Postoperative (PO) pain control, mobilization and physical therapies are the milestones of successful surgical outcomes. 4 However, some patients may report displeasure due to discordance with physical therapy and chronic pain. 5 It has been reported that psychological factors, such as pain catastrophizing and kinesiophobia, strongly influence pain perceptions and responses to physical activity, 6,7 which can lead to illness behaviour and subsequent disability characterized by poor cognitive and physical performance, such as disuse syndrome, anxiety, depression and decreased physical function, thus creating a vicious circle of pain and disability after musculoskeletal injury or surgery.…”
Section: Introductionmentioning
confidence: 99%